2015
DOI: 10.1016/j.gecco.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Political shifts and changing forests: Effects of armed conflict on forest conservation in Rwanda

Abstract: h i g h l i g h t s• Aspects of conflict can have very different impacts on forest cover. • Theoretical framework distinguishes armed conflict activity impacts from conflict settlements. • Forest transitions in NW Rwanda indicated more spatially concentrated loss during conflict. • 96% of forest loss during conflict across the landscape occurred in protected areas.• Results underscore heavy dependence on forest resources during conflicts. a b s t r a c tMost armed conflicts in recent history occurred in biodiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 52 publications
2
63
0
1
Order By: Relevance
“…The analysis of LCC trajectories and landscape fragmentation both at the class and landscape levels undertaken here has extended our understanding of LULCC in the WA [5, 7,9] and that of previous research on the impact of conflict on the environment [2,[11][12][13][14][15]. Our research provides the first detailed assessment of the extent and magnitude of landscape fragmentation and trajectory trends in the WA, findings that are useful to conservation planning and management efforts for WAPFoR.…”
Section: Discussionmentioning
confidence: 61%
“…The analysis of LCC trajectories and landscape fragmentation both at the class and landscape levels undertaken here has extended our understanding of LULCC in the WA [5, 7,9] and that of previous research on the impact of conflict on the environment [2,[11][12][13][14][15]. Our research provides the first detailed assessment of the extent and magnitude of landscape fragmentation and trajectory trends in the WA, findings that are useful to conservation planning and management efforts for WAPFoR.…”
Section: Discussionmentioning
confidence: 61%
“…Several reports relate this deforestation with nexus of timer mafia and combatant groups for financial gains and clearing by security forces for tactical reasons [58][59][60]. Deforestation along the western borders of Pakistan during last decade are similar to the deforestation patterns in Afghanistan during 1980-2000 and the spatially concentrated loss and heavy dependence on forest resources during the Rwandan conflicts [61,62]. The deforestation and degradation levels reported in this study need to be analyzed in terms of anthropogenic factors as reported in several other studies [55][56][57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…These political changes may have a greater effect on conservation than would many of the issues presented here. While specific geopolitical events can be unpredictable, we are aware that recent trends, including the rise in nationalism, military conflicts, terrorism, and the mass movements of political or economic migrants and refugees (e.g., [62]), can have considerable effects on biological diversity that we may fail to identify on an annual basis. At the same time, there are global desires and movements to improve living standards in low-income countries and to reduce the disparity between relatively high-income and low-income populations and nations.…”
Section: Discussionmentioning
confidence: 99%